Inca Mortuary Practices: Material Accounts of Death in Quebrada De Humahuaca at the Time of the Empire - Scaro, Agustina (2019)
This contribution has the purpose of presenting a set of material evidences linked to mortuary practices from Inca times recovered in Esquina de Huajra and Pucara de Tilcara archaeological sites. This in order to ponder the role of funerary practices in the social life of loca populations under Inca control. The presented contexts refer to diverse practices pointing at the great variability regarding the treatment of the deceased during Inca times, allowing to analyze the new socio-political context established in Quebrada de Humahuaca. The funerary practices registered refer to a strong tradition linked to the cult to the ancestors, probably rooting from pre-Inca moments. As in other Andean cases, these manifestations could have responded to beliefs associated with the regeneration of crops and productive cycles in general. The role of the deceased in strengthening the collective memory and the meaning of traditions shared throughout time is also relevant.